Trump and the death of the Image. Issue 1 (26th October 2020) - Appadurai, Arjun
Abstract : We would be wrong to imagine that Trump belongs in the long tradition of American politicians who are deeply concerned with managing their images. The idea of the image as a central feature of American life has been a popular axiom of the last seven decades and has not been adequately rethought. Trump has successfully found a following that likes him unvarnished and unadorned, and thus he has no hesitation to reveal his most repellent moral and social qualities. This indifference to the image is anchored in a deeper indifference to sociality itself and signals both the death of the image and the evacuation of any socially‐grounded morality from public life.